Comprehensive genomic analysis and expression profiling of cysteine-rich polycomb-like transcription factor gene family in tea tree - Hong Nan; Yanglei Lin; Xinghua Wang; Lizhi Gao (Horticultural Plant Journal, 2021)
Cysteine-rich polycomb-like (CPP) is a small gene family in plants, which plays key role in plant development and stress response. Although CPP transcription factors have been characterized in several other plant species, a genome-wide characterization of the CPP gene family has been absent in Camellia sinensis. In this study, we totally identified 7, 8, and 8 non-redundant CsCPP genes in three published genomes, including Camellia sinensis var. assamica cv. Yunkang-10 (CSA-YK10), Camellia sinensis var. sinensis cv. Biyun (CSS-BY) and Camellia sinensis var. sinensis cv. Shuchazao (CSS-SCZ). CPP proteins from tea tree and other plant species were classified into three groups, which were further divided into four subgroups based on phylogenetic relationships. Most CPP genes in the same subgroup had similar gene structures and conserved motifs. The cis-acting elements analysis indicated that CPP genes might be involved in plant growth, development and stress responses. Analysis of gene expression using qRT-PCR experiments validated that CPP genes exhibited different expression patterns across the examined tissues. All the genes were expressed differentially in a range of tissues, indicating that CPPs were involved in a range of developmental and physiological processes. This study has obtained new insights into the evolution and function of the CPP gene family in the growth and development of tea plants, and also provide candidate genes for further functional characterization in tea tree.